2020
DOI: 10.1111/ajo.13213
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pregnancy outcomes between natural cycles and artificial cycles following frozen‐thaw embryo transfers

Abstract: Background: Frozen embryo transfer (FET) is increasing in prevalence. In contrast to the amount of research performed on the actual cryopreservation procedure, there are limited data with respect to optimal endometrial preparation in FET cycles. Increasingly artificial cycle (AC) preparation is being adopted over the natural cycle (NC) to facilitate greater access to FET. However, there remains a paucity of data comparing pregnancy outcomes between these two commonly used cycle types. Aims: To examine the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…A recent large retrospective study by Pakes et al which analysed blastocyst thaw cycles, observed that the AC group experienced a higher pregnancy loss compared with the women in the NC group. 10 In this study, women in the AC group were significantly younger and received a higher proportion of good quality day-5 blastocysts compared with the NC which may have biased results to favour the AC, however, the AC group still demonstrated more pregnancy losses compared with the NC group.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…A recent large retrospective study by Pakes et al which analysed blastocyst thaw cycles, observed that the AC group experienced a higher pregnancy loss compared with the women in the NC group. 10 In this study, women in the AC group were significantly younger and received a higher proportion of good quality day-5 blastocysts compared with the NC which may have biased results to favour the AC, however, the AC group still demonstrated more pregnancy losses compared with the NC group.…”
Section: Discussionmentioning
confidence: 67%
“…We included nine studies in our final quantitative analysis. 10 16 20–26 Two of which were RCTs 22 23 both of which studied small sample sizes. The remaining seven were retrospective cohort studies, 10 16 20 21 24–26 which followed a much larger sample size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…both demonstrated non-inferiority in the NC-FET group compared to the AC-FET group [36,37]. As the group of women having AC could differ in cycle regularity, Cochrane (Ghobara et al, 2017) compared different protocols for FET for women with regular menstrual cycles and reported no differences in live birth rates or miscarriages between the two protocols [13].…”
Section: Effect Of Hormone Substitution On Fibrinolysismentioning
confidence: 99%